Essential role of NbNOG1 in ribosomal RNA processing. Issue 11 (5th September 2018) - Guo, Jiangbo; Han, Shaojie; Zhao, Jinping; Xin, Cuihua; Zheng, Xiyin; Liu, Yule; Wang, Yan; Qu, Feng
Summary: Nucleolar GTP‐binding protein 1 (NOG1) is a highly conserved GTPase first reported in Trypanosoma as required for ribosome biogenesis. We characterized NbNOG1, a Nicotiana benthamiana NOG1 ortholog sharing more than 45% amino acid identity with Trypanosoma, yeast, and human NOG1. N. benthamiana plants silenced for NbNOG1 were stunted and produced sterile flowers. NbNOG1 is functionally interchangeable with yeast NOG1 (ScNOG1), rescuing yeast lethality caused by loss of ScNOG1 . Finally, NbNOG1 silencing caused over‐accumulation of pre‐rRNA processing intermediates, and concomitant loss of mature rRNAs. Collectively, these data support a role for NbNOG1 in ribosomal RNA processing. Abstract : Nucleolar GTP‐binding protein 1 of Nicotiana benthamiana (NbNOG1) is implicated in pre‐rRNA processing and ribosome biogenesis in this study, through an array of investigations including virus‐induced gene silencing, determination of intracellular localization with fluorescent protein labelling, and profiling of pre‐rRNA processing intermediates.